Beyond integration? inter/disciplinary possibilities for the future of Christian higher education - Ream, Todd C.; Pattengale, Jerry A.; Riggs, David L. (David Lee), 1967- (Abilene, Tex. : Abilene Christian University Press, 2012)
The phrase "integration of faith and learning" has come to describe the way many Christian colleges and universities understand how all learning falls under the lordship of Jesus Christ. With its origins in the philosophical and theological insights of the Reformed tradition, this phrase has expanded its influence to institutions nurtured by numerous Christian traditions. This volume draws together prominent scholars who reflect on Christian higher education as it may exist beyond the integration model.
Foreword / John Wilson -- Introduction / Todd C. Ream, Jerry Pattengale, and David L. Riggs -- Beyond integration: re-narrating Christian scholarship in postmodernity / James K. Smith -- Healing democracy's discontent: the Christian contribution to contemporary politics / Jeanne Heffernan Schindler -- Why no Christian sociology? exploring the hidden history of an interdisciplinary conversation / John A. Schmalzbauer -- English beyond integration / David Lyle Jeffrey -- Evangelicals, the academy, and the discipline of history / Timothy Larsen -- Five uneasy questions: or, will success spoil Christian psychologists? / Mary Stewart Van Leeuwen and Jade Avelis -- Christianity, science, and the history of science: some thoughts on the integration of faith and learning / Edward B. Davis -- Beyond the disciplines, God: the study of the Christian Scriptures and the formation of a faithful habitus for truthful learning / John W. Wright -- Conclusion / Jerry Pattengale -- Epilogue / Henry L. Smith.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christian universities and colleges -- United States; Christian education -- United States; Interdisciplinary approach in education -- United States; Christian education; Christian universities and colleges; Interdisciplinary approach in education; United States; EDUCATION / Higher; Electronic books